1998
DOI: 10.1002/(sici)1097-4636(199824)43:4<422::aid-jbm9>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymer concepts in tissue engineering

Abstract: Traumatic injuries, cancer treatment, and congenital abnormalities are often associated with abnormal bone shape or segmental bone loss. Restoration of normal structure and function in these cases requires replacement of the missing bone that may be accomplished by surgical transfer of natural tissue from an uninjured location elsewhere in the body. However, this procedure is limited by availability, adequate blood supply, and secondary deformities at the donor site. One strategy to overcome these problems is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
205
1
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(211 citation statements)
references
References 15 publications
0
205
1
5
Order By: Relevance
“…Microporous polycaprolactone (PCL) matrice with various pore sizes might be used to stimulate osteogenesis by delivery of various protein such as lysozyme (100-200 lm), collagenases (80-200 lm), catalase (100-250 lm), lactose (45-90, 90-125 lm) and gelatin (125-250 lm) into damaged tissue (Wang et al , 2009). Correspondingly, osteoblasts proliferation and bone formation on the PLGA scaffold was the best with the poresize ranging from 150 to 300 lm (Peter et al 1998). Parallelly, it was shown that PLGA scaffolds with pore size ranging from 150 to 710 lm had no impact on the osteoblasts attachment and proliferation, whereas tissue mineralization was the best on the scaffolds with 300-500 lm pores (Ishaug et al 1997).…”
Section: Pore Sizes Regulating Bone Regenerationmentioning
confidence: 99%
“…Microporous polycaprolactone (PCL) matrice with various pore sizes might be used to stimulate osteogenesis by delivery of various protein such as lysozyme (100-200 lm), collagenases (80-200 lm), catalase (100-250 lm), lactose (45-90, 90-125 lm) and gelatin (125-250 lm) into damaged tissue (Wang et al , 2009). Correspondingly, osteoblasts proliferation and bone formation on the PLGA scaffold was the best with the poresize ranging from 150 to 300 lm (Peter et al 1998). Parallelly, it was shown that PLGA scaffolds with pore size ranging from 150 to 710 lm had no impact on the osteoblasts attachment and proliferation, whereas tissue mineralization was the best on the scaffolds with 300-500 lm pores (Ishaug et al 1997).…”
Section: Pore Sizes Regulating Bone Regenerationmentioning
confidence: 99%
“…However, there are studies that argue that smaller pore sizes may be adequate for bone growth 45 and that pore sizes in the 150-710 µm range do not have any significant effect on osteoblast behavior. 43,44,75 Although results vary, an important underlying trend is the need for scaffolds to have a high porosity.…”
Section: Scaffolds Fabricated Via Sff/rp Techniquesmentioning
confidence: 99%
“…Since non-biodegradable polymers would interfere with tissue turnover and remodeling, the current trend is to use biodegradable polymers in tissue engineering, although the non-biodegradable polymers have the advantage that their properties, both chemical and mechanical, are less aVected by the cellular and tissue milieu. On the other hand, polymer biodegradation via the combined eVect of enzymatic and hydrolytic activities generates space within the scaVold to allow for cell proliferation and the deposition of newly synthesized ECM [3]. Ideally, optimal tissue regeneration occurs upon complete biodegradation of the polymeric matrix followed by restoration of biological functions.…”
Section: Introductionmentioning
confidence: 99%